"Zu grob gewest": Metainvective Communication in Confessional Disputes over Narration of the Saints in the Sixteenth Century - Sablotny, Antje (Journal of Early Modern Christianity, 2023)
The article is devoted to coarse uses of language as a subject of dispute in confessional controversies over legendary narration. Such metainvective forms of communication are systematized, and questioned with regard to their functions: in the Protestant Lügenden (word combination of "legend" and "lie," lying legends) and their Catholic replies, the "true" faith and its defense are connected with communicative behavior. Whereas Lutherans are above all effective at adopting coarse speech and the metainvective reproach of lying, the Counter-Reformation argumentation develops the strategic potential of metainvective communication in very different ways. Metainvective statements become a weapon particularly when they are absorbed into figures of meta-metainvective, which not only display the coarse speech but reveal and then criticize the strategy behind it. The tension between polemical prefaces and annotated miracle narratives in the Lügenden as well as the thematic proliferation of the legend discussion in the Catholic reports and sermons are ultimately shown to be genre-dynamic effects of the use of metainvectives.